RELATION BETWEEN SELF-REGULATED LEARNING AND ACADEMIC ACHIEVEMENT OF SENIOR SECONDARY STUDENTS - Bhagwat, Sarika Vinayakrao; Sadaphal, Ujjwala Dhanjay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the relationship between self-regulated learning (SRL) and academic achievement among 11th standard students from Nagpur and Wardha districts. A sample of 300 students was selected using a stratified random sampling technique. Data were collected using a standardized SRL scale and academic scores from recent examinations. The analysis, using Pearson’s correlation and t-test, revealed a significant positive correlation between SRL and academic achievement. Moreover, female students exhibited significantly higher SRL scores than their male counterparts. The findings highlight the importance of fostering SRL skills in adolescents to enhance academic performance. The study suggests that educators, policymakers, and parents should collaboratively promote goal setting, time management, and reflective practices among learners.